On the Frequencies for Structural Health Monitoring in Plates with Asymmetrical Damage: An Analytical Approach - Lopes, Kayc W. [UNESP]; Gonsalez-Bueno, Camila G. [UNESP]; Inman, Daniel J.; Bueno, Douglas D. [UNESP] (SPIE, the international society for optics and photonics, 2022)
Detecting incipient damage in structures is an important challenge for the engineering community. The design of structural health monitoring (SHM) systems usually involves selection of actuators and sensors, defining their positions on the structure and post-processing output signals. Another important task is to define the characteristics of the excitation signals before investigating the structural condition. In this context, the present article introduces an approach to determine the optimal frequencies for asymmetrical damage detection in plates considering perpendicular incidence of longitudinal and flexural waves incoming in the damage. At these optimal frequencies are observed the maximum reflected and the minimum transmitted wave amplitudes. In both cases of incidence, it is noted that the first maximum and minimum wave amplitudes have optimal frequencies close to those obtained when there is no damage asymmetry. It is also demonstrated that the pulse-echo configuration is more convenient for damage detection because it involves higher wave amplitude variations than the pitch-catch configuration. Numerical simulations are carried out by considering an aluminum plate, and the results show that the approach contributes to the establishment of more efficient SHM systems.
Keywords: Asymmetrical Damage; Longitudinal and Flexural Waves; Optimal Frequencies; Thin Plates; Wave Propagation